High-temperature metasurface for polarization conversion and RCS reduction - Wang, Wenjie; Jiang, Jinming; Liang, Jiangang; Zheng, Lin; Meng, Yueyu; Li, Yongfeng; Xu, Cuilian; Wang, Jiafu; Qu, Shaobo (Frontiers in Physics, 2022)
In this paper, we present a high temperature-resistant linear-to-linear polarization conversion metasurface for wideband RCS reduction in the microwave regime. Linear-to-linear polarization conversion metasurface is composed of a single layer of high temperature resistant metallic pattern array. When linearly polarized waves impinge on the metasurface, the polarization conversion rate is greater than 90% from 9 GHz to 16.9 GHz at 800℃. The polarization conversion unit arrangement forms a checkerboard configuration metasurface, which can effectively reduce RCS reflection. The wideband RCS reduction mechanism is scattering cancellation rather than absorption. The metasurfaces were designed, fabricated and measured, which can realize linear-to-linear polarization conversion and wideband RCS reduction. Simulation and measurement results are all in good agreement. Meanwhile, the measurement provides a solid verification for our design. The results provide an alternative method to reduce the RCS at high temperatures.